# Bretschneider's formula

Bretschneider's formula gives the area of a quadrilateral, \(\Delta\), by the following formula:

\[\Delta^{2} = (s-a)(s-b)(s-c)(s-d)-abcd\cos^{2}\left(\frac{B+D}{2}\right).\]

Notation:Let \([X]\) represent the area of a polygon (here, a triangle or a quadrilateral). Also let \(\Delta = [ABCD]\), and let \(AB=a\), \(BC=b\), \(CD=c\), \(DA=d\). Let \(s\) be the semiperimeter of the quadrilateral \(ABCD\), given by \(s=\dfrac{a+b+c+d}{2}\).

Construction:Join \(\overline{AC}\).

Proof:We have

\[\begin{align} [ABCD] &= [ABC] + [ACD] \\ \Delta &= \frac{1}{2}ab\sin B + \frac{1}{2}cd\sin D \\\\ \Rightarrow \ 2ab\sin B + 2cd\sin D &= 4\Delta \qquad {\color{blue} (1)} \end{align}\]

Now we will use cosine rule to find \(AC\) in two ways, once using \(\Delta BAC\) and once using \(\Delta DAC\).

\[\begin{align} AC^{2} &= a^{2} + b^{2} - 2ab\cos B \\ &= c^{2} + d^{2} - 2cd\cos D \\\\ \Rightarrow \ 2ab\cos B - 2cd\cos D &= a^{2} + b^{2} - c^{2} - d^{2}. \qquad {\color{blue} (2)} \end{align}\]

Squaring and adding equations \({\color{blue} (1)}\) and \({\color{blue} (2)}\), we have

\[\begin{align} 4a^{2}b^{2}+4c^{2}d^{2} - 8abcd(\cos B \cos D - \sin B \sin D) &= 16\Delta^{2} + \big(a^{2}+b^{2} - c^{2}-d^{2}\big)^{2} \\ 4a^{2}b^{2}+4c^{2}d^{2}-8abcd\cos(B+D)&=16\Delta^{2}+\big(a^{2}+b^{2}-c^{2}-d^{2}\big)^{2} \\ (2ab+2cd)^{2}-8abcd-8abcd\cos(B+D)&=16\Delta^{2}+\big(a^{2}+b^{2}-c^{2}-d^{2}\big)^{2} \\ (2ab+2cd)^{2}-8abcd\big(1+\cos(B+D)\big)&=16\Delta^{2}+\big(a^{2}+b^{2}-c^{2}-d^{2}\big)^{2}. \end{align} \]

Then

\[\begin{align} 16\Delta^{2} &= (2ab+2cd)^{2}-\big(a^{2}+b^{2}-c^{2}-d^{2}\big)^{2}-8abcd\times 2\cos^{2}\left(\frac{B+D}{2}\right) \\ &=\big(2ab+2cd+a^{2}+b^{2}-c^{2}-d^{2}\big)\times\big(2ab+2cd-a^{2}-b^{2}+c^{2}+d^{2}\big)-16abcd\cos^{2}\left(\frac{B+D}{2}\right) \\ &=\big((a+b)^{2}-(c-d)^{2}\big)\big((c+d)^{2}-(a-b)^{2}\big)-16abcd\cos^{2}\left(\frac{B+D}{2}\right) \\ &=(a+b+c-d)(a+b-c+d)(a-b+c+d)(-a+b+c+d)-16abcd\cos^{2}\left(\frac{B+D}{2}\right) \\ &=(2s-2d)(2s-2c)(2s-2b)(2s-2a)-16abcd\cos^{2}\left(\frac{B+D}{2}\right) \\ &=16(s-a)(s-b)(s-c)(s-d)-16abcd\cos^{2}\left(\frac{B+D}{2}\right) \\\\ \Rightarrow & \Delta^{2}=(s-a)(s-b)(s-c)(s-d)-abcd\cos^{2}\left(\frac{B+D}{2}\right), \end{align}\]

which is the Bretschneider's formula. \(_\square\)

Also see the pages on cyclic quadrilaterals and Brahmagupta's formula.

**Cite as:**Bretschneider's formula.

*Brilliant.org*. Retrieved from https://brilliant.org/wiki/bretschneiders-formula/